(untitled) (Revista Electrónica REDINE, 2018)
This study is framed in an investigation of descriptive field, the same had to describe the importance of research through ICT in higher education. This research is focused on various theoretical underpinnings that allow an outline of the technological theories covering many top-level research. The subjects of this study was made up of sixty-five (65) students who completed educational research UPEL -IPB. At which was applied an instrument to collect information that allowed us to establish the importance of research through the use of information and communications technology at the top level. The analysis of the results indicates that students always use these technologies to develop a broader field of study in its investigation, besides the contribution that these give to the development of their projects. Added to this, recommend applying ICT to ensure the interaction of various sources of knowledge.